Case report: Sagliker syndrome in the patient with recurrent tertiary hyperparathyroidism due to intrathyroidal parathyroid carcinoma - Salimkhanov, Rustam; Bondarenko, Ekaterina; Eremkina, Anna; Bibik, Ekaterina; Kim, Ekaterina; Begova, Kamila; Kim, Ilya; Kuznetsov, Sergey; Mokrysheva, Natalia (Frontiers in Endocrinology, 2024)
Sagliker syndrome (SS) is an extremely rare disorder that manifests in patients with advanced chronic kidney disease (CKD) undergoing programmed hemodialysis as a renal replacement therapy. Treatment of secondary hyperparathyroidism (SHPT) in these patients is still challenging. The main clinical manifestations of SS include craniofacial and fingertip deformities, dental anomalies, gingival hyperplasia, short stature, hearing loss, neurological and psychiatric impairment. The etiology and pathogenesis of SS in patients with SHPT require further clarification. However, mutations in the GNAS1, FGF23, and FGFR3 genes were described in some patients, suggesting a possible role of genetic predisposition to the syndrome. The preferred therapeutic approach for SS is surgery, but the volume of the operation is debated. The main surgical strategies include total, subtotal parathyroidectomy, or total parathyroidectomy with autotransplantation of the parathyroid gland (PG). Unfortunately, parathyroidectomy does not contribute to the regression of significant skeletal deformities. We present a unique clinical case of a patient with classical features of SS, recurrent tertiary hyperparathyroidism (THPT) after total parathyroidectomy due to intrathyroidal parathyroid carcinoma (PC).